Методы энергосбережения в сахарной промышленности (Обзор) - Болдырев, Станислав Александрович (НТУ "ХПИ", 2007)
Energy saving methods for sugar industry are described. The last tendencies of retrofit and modernization of sugar plants are considered. Energy consumption of European sugar plants is compared with Ukrainian level. Energy saving potential of Ukrainian sugar plants with help of process integration and modern heat exchange equipment are defined.
Keywords: модернизация сахарных изделий; энергозатраты; энергосбережение